Pengembangan Media Pembelajaran Berbasis Flash Mx Pada Mata Pelajaran Muhadatsah - Farida Nur Jannah; M. Dzikrul Hakim Al Ghozali (Institut Agama Islam Negeri (IAIN) Metro, 2020)
The research using the ADDIE went through these phases: (1) Analysis Phase was problem analysis, material analysis, learners character analysis, learning purpose, and learners need. (2) The design phase was making the media in Microsoft PowerPoint and steps of producing media in Flash MX. (3) Development Phase was validating the product to material expert and media expert. (4) The implementation phase was practicing for the class tent of MA Al-I'dadiyyah Bahrul Ulum learners with 22 learners to do effectiveness test, which is pre and post-test after Macromedia Flash MX based learning media was given. (5) Evaluation Phase was to see the effective and evaluation was extracted from learners response. The validated media according to assessment from material expert validation (Arab Language Department's Lecturer) was 4,1 with very valid category, evaluation from the material expert (muhadatsah course teacher) was 4,6 with very accurate class, whereas media expert was 3,7 with correct category and learners response as much as 87% with very agree to category. Effectiveness test was from normality test, homogeneity test, and simple paired t-test concluded that Ha accepted than Ho rejected means Macromedia Flash MX used media development was effective in muhadatsah learning in the tenth class of MA Al-I'dadiyyah.